Soils : genesis and geomorphology - Schaetzl, Randall J., 1957-; Thompson, Michael L. (Cambridge Cambridge university press, 2015)
"In its first edition, Soils established itself as the leading textbook in the fields of pedology and soil geomorphology. Expanded and fully updated, this second edition maintains its highly organized and readable style. Suitable as a textbook and a research-grade reference, the book's introductory chapters in soil morphology, mineralogy, chemistry, physics, and organisms prepare the reader for the more advanced treatment that follows. Unlike its competitors, this textbook devotes considerable space to discussions of soil parent materials and soil mixing, along with dating and paleoenvironmental reconstruction techniques applicable to soils. Although introductions to widely used soil classification systems are included, theory and processes of soil genesis and geomorphology form the backbone of the book. Replete with more than 550 high-quality figures and photos and a detailed glossary, this book will be invaluable for anyone studying soils, landforms, and landscape change anywhere on the globe"--
Machine generated contents note: Part I. The Building Blocks of Soils: 1. Introduction; 2. Basic concepts: soil morphology; 3. Basic concepts: soil horizonation... the alphabet of soils; 4. Basic concepts: soil mineralogy; 5. Basic concepts: soil chemistry; 6. Basic concepts: soil physics; 7. Basic concepts: soil organisms; 8. Soil classification and mapping; 9. Weathering; Part II. Soil Genesis: From Parent Material to Soil: 10. Soil parent materials; 11. Pedoturbation; 12. Models and concepts of soil formation; 13. Soil genesis and profile differentiation; Part III. Soil Geomorphology: 14. Soil geomorphology and hydrology; 15. Soil development and surface exposure dating; 16. Soils, paleosols, and paleoenvironmental reconstruction; 17. Conclusions.
Includes bibliographical references and index.
Keywords: Soils; Soil formation; Soil structure; Geomorphology; TECHNOLOGY & ENGINEERING / Agriculture / Agronomy / Soil Science